Akhond Khorasani's viewpoints towards the modern concepts of freedom and justice - Soroush, Alireza; Sandhu, Sarvinder Kaur; Alaei, Hamed (Marsland Press, 2010)
This article seeks to understand the mentality of Akhond Khorasani, the leader of the Iranian constitutional revolution (1905-1911) regarding the political and social concepts such as freedom and justice. In the Iranian society, concepts such as freedom and justice were always affected by various kinds of understanding and comprehension. These concepts were never interpreted based on their original and true meanings which are essentially the principles of democracy. In other words, the Iranian society was faced some problems and difficulties in absorbing these concepts and it seems even nowadays these concepts do not possess their true meaning in the political social culture of Iran and everybody explain them based on their own personal assumptions and subjectivity. It is for this reason that Iran has not had much of a practical experience from the existence of these concepts and achieving such and experience needs more time. Understanding the opinions of Akhond Khorasani (the revolution’s leader) vis-à-vis these concepts can be an indication of the formation of democracy’s pillar in Iran and also an indication of how the clergy faced these concepts, understand them and what practical ways they used to realize them. The theoretical framework of this article is based on the modernity theory. In essence, modernity comprises the theoretical aspects of the entire social, political, economical and cultural issues and guide human societies through the passageway of tradition to the modern world. The methodology used in this study is the unobtrusive research methodology, since this is a qualitative and historical research. The content analysis method which is one of the methods used in qualitative and historical researchers has also been implemented in this research.